2021
DOI: 10.3390/admsci11030069
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and People Management: The View of Human Resource Managers

Abstract: COVID-19 has brought an unexpected need for change within organizations, particularly regarding human resource management. The nature of this global crisis has meant that these processes remain under-systematized. The aim of this study, which uses an exploratory design and mixed-methods analysis, is to contribute to describing the changes in human resource management practices and processes that resulted from this pandemic and to present the outlook of human resource managers for the future. One hundred and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 16 publications
0
8
0
1
Order By: Relevance
“…The perception of control that the worker has over his or her work influences work planning, work speed, and goal setting, as pointed out by Chung (2017). Moreover, since studies have shown that a high level of autonomy at work can reduce the conflict between family and work (Goldstein 2003;Voydanoff 2004), this is an important dimension to be considered when work is shifted to telework. While support from the supervisors and from coworkers did not predict the work-family conflict, they proved to have a moderating effect on after-hours work-related technology use and work-family conflict.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The perception of control that the worker has over his or her work influences work planning, work speed, and goal setting, as pointed out by Chung (2017). Moreover, since studies have shown that a high level of autonomy at work can reduce the conflict between family and work (Goldstein 2003;Voydanoff 2004), this is an important dimension to be considered when work is shifted to telework. While support from the supervisors and from coworkers did not predict the work-family conflict, they proved to have a moderating effect on after-hours work-related technology use and work-family conflict.…”
Section: Discussionmentioning
confidence: 99%
“…This perception of control that the worker has over his or her work influences work planning, work speed, and goal setting (Chung 2017). A higher level of autonomy at work can reduce the conflict between family work, as suggested by studies conducted in salaried workers (Voydanoff 2004) and teleworkers (Goldstein 2003). This reduction in the conflict between family work may be because employees believe that they have the necessary competence and capabilities to achieve their job performance (Saragih 2011).…”
mentioning
confidence: 99%
“…Furthermore, the third indicator, Human Resources, is an important indicator that can run the organization’s services technically. Scientific articles that are in line with this indicator as mentioned ( Shrouf et al, 2020 ; Gonçalves et al, 2021 ; Murawski, 2021 ). This indicator is indicated by eight components which are detailed in (3.1) Recruitment, staff diversity, and expertise; (3.2) Roles, responsibilities, and job descriptions; (3.3) Personnel files; (3.4) Timesheets; (3.5) Volunteer/Internal management; (3.6) Discipline, grievances, and conflict resolution; (3.7) Staff performance evaluation; and (3.8) Development staff.…”
Section: Resultsmentioning
confidence: 95%
“…That traditional and indigenous technology is not able to produce food in large quantity. Besides that, the use of technology also emerges in processes such as recruitment and selection or training and development (Gonçalves et al, 2021). One of the implementations of development is the application of information technology for the effectiveness of work.…”
Section: Human Resource Management In the Management Of Food Barns Du...mentioning
confidence: 99%